How different types of environmentalists are perceived: changing perceptions by the feature - Kibele, Karolin; Rosa, Miriam; Obaidi, Milan (Frontiers in Psychology, 2023)
Previous research found stereotypes of environmentalists as barriers to public engagement and identification with environmentalism. Yet, there's limited understanding of the distinct attributes of an environmentalist that influence public perceptions and self-identification. In our research, we address this knowledge gap by analyzing reactions to a range of fictional environmentalist profiles. We investigated how multiple features of these profiles (e.g., gender, occupation, type of pro-environmentalism) influenced stereotypes (such as competence, friendliness, and trustworthiness), perceived typicality, and participants’ self-identification with the described profiles. Using a novel conjoint experiment approach with 678 U.S. residents, we found that profiles described as women, Asians, working as a cleaner or office clerk, and politically moderate or liberal, exhibiting private to moderate environmental behaviors and global environmental concerns, were generally perceived as more typical for environmentalists. Moreover, participants most identified with profiles depicted as women, in a cleaner occupation, and exhibiting private pro-environmental behaviors. Atypical profile descriptions, based on prior research, enhanced participants' impressions only when associated with private pro-environmental behaviors or the cleaner occupation. We introduce new avenues in impression formation research and the use of conjoint analyses in psychological research; moreover, we contribute valuable input to the environmental movement regarding message framing considering the source and content relative to the targeted audience.